Empower users of financial information as the IASC Foundation's stakeholders: Testimony to the IASC Foundation's Constitution Review Round Table in London, 19 June 2008 - Nicolas Véron (Bruegel, 2008)
Nicolas Véron comments on the proposal for governance reform ('constitution review') published in May 2008 by the IASC Foundation, the private-sector body which oversees the setting of International Financial Reporting Standards (IFRS). He emphasizes the unprecedented nature of this global governance experiment and advocates for more direct representation of investors as the primary stakeholders of international accounting standard-setting, as well a more thorough consultation process.
Keywords: 330; Aufsichtsrat; Nonprofit-Organisation; Betriebliches Rechnungswesen; Grundsätze ordnungsmäßiger Buchführung